TINJAUAN HUKUM ISLAM TERHADAP PERKAWINAN WANITA HAMIL: STUDI KASUS DI KANTOR URUSAN AGAMA KECAMATAN PASAR KLIWON KOTA SURAKARTA - Wijang Satoto; S Syamsudin; S Sugiyat (MAMBA'UL 'ULUM, 2023)
The purpose of this study was to determine the process of registering a pregnant woman's marriage and reviewing Islamic law on the implementation of a pregnant woman's marriage at the Office of Religious Affairs (KUA) in Pasar Kliwon District, Surakarta City. This research is a qualitative research with the research subject being the Head of KUA, Pasar Kliwon District, Surakarta City. Data was taken using observation, interviews and documentation. While data analysis by means of data reduction, data exposure and draw conclusions.The results of this study are that the process of registering a pregnant woman's marriage registration is the same as the marriage procedure for women in general or women who are not pregnant, it's just that in a closed forum (jonggolan) the head of the kua gives requirements containing that he is the man who actually got her pregnant and written on a stamp of 6,000. Then a review of Islamic law on the Implementation of Marriage for pregnant women at the Office of Religious Affairs in Pasar Kliwon District, Surakarta City for a woman who is pregnant can be married as long as the person who is married is a man who actually gets her pregnant, in accordance with the opinion of the majority of scholars' and article 53 Paragraph 1 KHI as for a widow who is pregnant may not be married unless she is allowed to be married as long as she has given birth.